Tropical vegetables conserved by fermentation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Fermentation is a biological method of preparing and preserving food which makes use of the bacteria and yeasts that are naturally present on fresh produce. It is one way of using up a seasonal glut in production and of conserving vegetable waste...